Learning Analytics: an Updated View - Šereš, Laslo; Pavlićević, Veselin; Petrović, Goran (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
Learning analytics has been a hot topic in the education industry for several years. Given its diverse roots (business intelligence, web analytics, educational data mining, etc.), researchers and practitioners have approached learning analytics from a range of perspectives. Although many studies concerning learning analytics have highlighted its great potential for improving learning practice, there has not been much success in the transfer of the suggested potential into the practice of higher education. This clearly indicates a need for rethinking not only the goals that can be achieved using learning analytics, but also what must be done in order to attain these goals. The aim of the descriptive research presented in this paper is to provide an honest and updated view of where we are, the real benefits, and the challenges to be overcome when using learning analytics as educational technology. This paper emphasizes that a deeper understanding of students’ learning experiences as well as a more realistic approach to both the interconnected concepts of learning analytics and the organizational practices that it supports can dramatically accelerate the improvement of student success at institutions.